ABORTION AMONG WOMEN VICTIM OF SEXUAL VIOLENCE: CONFLICTS AND CHALLENGES - Prata, Maiky Carneiro da Silva; Campos, Renata Sanzovo Pires de; Souza, Laila Batata Lopes Nunes de; Fernandes, Gustavo Leme; Hime, Lúcia de Fátima Cahino da Costa (Journal of Health Care, 2015)
Abortion is often associated with sexual coercion in Brazil. Objective: To reflect on abortion among womenvictims of sexual violence from the point of view of women, health professionals and the current legislationin Brazil. Methods: A narrative review (2004-2014) through MEDLINE and LILACS data basesvia PubMed. Descriptors: "gender", "vulnerability", "women", "induced abortion" and "sexual violence".Development: The inequality of gender favors violence against women. Although we have in the countrylaws guaranteeing the right of sexually abused women to abort, there is still a gap between the law and itsapplication. Moral and religious principles incorporated into the Brazilian education favors disrespect ofwoman rights even by health professionals. The lack of knowledge about this topic in the health professionals'background as well as about protocols of sex offenses against woman implies difficulty to treat thisfact as a public health problem. To recognize women violence as a public health problem is a challenge thatinvolves the incorporation of new professional habits. Conclusion: This study contributed to understandthe conflicts between women victims of sexual violence and professionals that work directly with abortionin Brazil, promoting health equity training and women's reproductive rights.
Keywords: Gender and health; health vulnerability; women; induced abortion and sexual violence.